Controle minoritário - Freitas, Rafael Guarilha P. de (2015)
This work aims to analyze and explore the controversial and relevant aspects inserted in the context of the working control, giving special emphasis to the aspects related to the mandatory bid rule and to the responsibility of the controlling shareholder for the misuse of his control power. Therefore, we have analyzed (i) the origin and the economic justification of the pattern of dispersion of the company s capital stock, which permits the appearance of the working control; (ii) the dynamism of the corporate control; (iii) the main aspects associated to the definition of the working control; (iv) the mandatory bid for the changing of the corporate control; (v) the responsibility of the minority shareholders for the misuse of the corporate power